Evidence of paleo-cold seep activity from the Bay of Bengal, offshore India - Mazumdar, A.; Dewangan, P.; Joaeo, H. M.; Peketi, A.; Khosla, V. R.; Kocherla, M.; Badesab, F. K.; Joshi, R. K.; Roxanne, P.; Ramamurty, P. B.; Karisiddaiah, S. M.; Patil, D. J.; et al. (Geochemistry, Geophysics, Geosystems, 2009)
We report evidence of paleo-cold seep associated activities, preserved in methane-derived carbonates in association with chemosynthetic clams (Calyptogena sp.) from a sediment core in the Krishna-Godavari basin, Bay of Bengal. Visual observations and calculations based on high-resolution wet bulk density profile of a core collected on board R/V Marion Dufresne (May 2007) show zones of sharp increase in carbonate content (10-55 vol%) within 16-20 meters below seafloor (mbsf). The presence of Calyptogena clam shells, chimneys, shell breccias with high Mg calcite cement, and pyrite within this zone suggest seepage of methane and sulfide-bearing fluid to the seafloor in the past. Highly depleted carbon isotopic values (delta C-13 ranges from -41 to -52% VPDB) from these carbonates indicate carbon derived via anaerobic oxidation of methane. Extrapolated mean calendar age (similar to 58.7 ka B. P.) of the clastic sediments at a depth of 16 mbsf is close to the upper limit of the U-Th based depositional age (46.2 +/- 3.7 and 53.0 +/- 1.6 ka) of authigenic carbonates sampled from this level, thereby constraining the younger age limit of the carbonate deposition/methane expulsion events. The observed carbonate deposition might have resulted from the flow of methane-enriched fluids through the fracture network formed because of shale diapirism.